THE INVOLVEMENT OF PARENTS FOR THE ROLE OF THE DRUG ABUSE PREVENTION AMONG TEENAGERS IN MUHAMMADIYAH HIGH SCHOOL OF GOMBONG KEBUMEN - Marsito, M (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
According to the Foundation of Yayasan Cinta Anak Bangsa (YCAB in Jakarta, 7% of teens aged 12 to 19 years had been claimed for drug abuse trial. a preliminary study to the numbers of education personnels and high school students of Muhammadiyah High School of Gombong,Â  11.5% o 40 staff personnel employees had ever tried drug abuse. The study was aimed to identify the correlation between the role of parent to the prevention of drug abuse of the high school of Muhammadiyah Gombong. This study used descriptive correlation design with cross sectional approach to variables consisting of the independent variable of student's home and the role of parents. The dependent variable is the drug abuse prevention. Total sample consisted of 186 adolescents aged 13 to 21 years taken by using accidental sampling technique. The analysis used univariate and bivariate analysis with chi square test.The results found that there was no correlation between the parents' involvement with drug abuse prevention where p = 0.856, there was a correlation between role's and the drug abuse prevention with p = 0.000.Thus the role of parents needs to be enhanced by giving education about the danger of drug abuse. It is necessary to remind the role of parents in family to educate the children about the danger of drug abuse and to give good examples and become true role models for their children at home and daily life Keywords: the role of parents, and the prevention of drug abuse, teenagers.